Pathological fracture of subtrochanter femur, soft tissue infection along the fracture site, shaft femur bone cortex thickening and blastic lession on contralateral shaft femur due to renal osteodystrophy on the end stage renal disease patient: a case report - Andika, Gde Dedy; Nugraha, Gede Ketut Alit Satria; Sunaria, I. Made; Astawa, Putu; Wiratnaya, I Gede Eka; Maharjana, Made Agus (International Journal of Research in Medical Sciences, 2020)
Renal osteodystrophy (ROD) is a skeletal complication resulting from pathologic alterations in calcium, phosphate, and bone metabolism. The potential link between bone turnover and bone quality is an important question meriting study because of the relatively high incidence of fractures reported. In this case presents a pathological fracture on a routinely hemodialyzed woman. She complained pain on her left subtrochanteric area after low energy trauma accident. A thickening of the shaft femoral bone cortex was also found, reflecting the osteosclerosis event due to imbalance of proliferation and differentiation of osteoblast with increase bone formation. She also had a blastic lesion on her contralateral shaft femoral during the bone survey, but this finding remains asymptomatic. Decreased osteoclastic activity may contribute to cortical thickening, resulting in overall bone mass increase, which may lead to decreased elasticity of the bone or impaired repair capabilities, therefore increasing the risk of fracture. The blastic lesion that occurred on contralateral side may indicated effect of ROD or primary bone lesion. Careful assessment and holistic management of patients with kidney disease is necessary to achieve optimal outcome. The prevention of falls is also an important strategy to prevent pathological fractures. End stage renal disease (ESRD) have reduced bone mineral density, a risk factor for fracture incidence. Careful anamnesis and clinical examination are needed for diagnosis and management.